(untitled) (Annals of Medical Research, 2024)
Aim: To determine and compare the post-earthquake trauma levels of hemodialysis (HD) patients, healthcare professionals working in the HD unit, and peritoneal dialysis (PD) patients in the 11th month of two earthquakes that occurred approximately nine hours apart on February 6, 2023, and affected the east and southeast regions of Turkey. Materials and Methods: The study included a total of 162 individuals, including 87 HD and 35 PD patients who had experienced both earthquakes, and 40 healthcare professionals working in the HD unit. The post-earthquake trauma levels of the participants were assessed using the Scale That Determines the Level of the Trauma After the Earthquake (SDLTAE), consisting of a total of 20 items, developed by Tanhan et al. after the 2011 Van earthquake. The individuals with an SDLTAE score of >52 were considered highly traumatized. Results: The mean age of the participants was 53±16 years, and 79 (49%) were women. The SDLTAE score of the HD patients was found to be higher than that of the PD patients (p=0.006). There were no significant differences between the SDLTAE scores of the healthcare professionals and the HD and PD patients (p=0.419 and p=0.089, respectively). Upon comparing patients with low and high total SDLTAE scores, we observed that the rate of female individuals was higher in all groups (p<0.001 for the HD and PD groups; p=0.017 for healthcare professionals). No correlation was found between the total SDLTAE score and age, dialysis duration, or laboratory parameters between the HD and PD patients (p>0.05). Conclusion: We found that HD patients had a higher level of trauma than PD patients. Our study showed that women were more traumatized than men in sensitive groups, such as those receiving dialysis and healthcare professionals. Regularly conducting psychological assessments for dialysis patients and healthcare professionals may increase the likelihood of early intervention.